2007
DOI: 10.3141/2004-09
|View full text |Cite
|
Sign up to set email alerts
|

Review of Lightweight Deflectometer for Routine in Situ Assessment of Pavement Material Stiffness

Abstract: • This is a journal article. It was published in the journal, Transportation Fleming, Frost, and Lambert 2 ABSTRACT The use of a portable lightweight deflectometer (LWD) for construction quality control or material investigation for earthworks and road construction is increasing around the world. This paper reviews the LWD as a field evaluation tool, discusses the test variables and data quality and concludes both on its usefulness and also its limitations for a variety of earthwork and road assessment scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 6 publications
0
44
0
3
Order By: Relevance
“…In other words, the relationship between CBR and PFWD modulus appears to be difficult to be defined for low-strength materials. This could be a reasonable agreement indicating poor correlation between CBR and E PFWD in another study where seventeen samples of all the CBR tests (eighteen samples) had values less than 25% (Seyman 2003). Indeed, CBR test is a strength evaluating testing method for soft materials.…”
Section: Fig 6 a Zero Intercept Regression Analysis Between Cbr Andmentioning
confidence: 73%
See 2 more Smart Citations
“…In other words, the relationship between CBR and PFWD modulus appears to be difficult to be defined for low-strength materials. This could be a reasonable agreement indicating poor correlation between CBR and E PFWD in another study where seventeen samples of all the CBR tests (eighteen samples) had values less than 25% (Seyman 2003). Indeed, CBR test is a strength evaluating testing method for soft materials.…”
Section: Fig 6 a Zero Intercept Regression Analysis Between Cbr Andmentioning
confidence: 73%
“…Phillips and Freeman (2003), Nazzal (2003) and George et al (2009) showed that there is good correlation between these parameters; whereas, poor correlation was reported in some other research works (Seyman 2003;Phillips 2005). In addition, different correlations have been determined between the PFWD and FWD back-calculation moduli (Steinert et al 2006;George 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in compatibility/correlations between LWD devices and correlations to FWD stiffness has been observed, and these are observed to be material and site specific, as a function of the type of buffers and pulse duration, depth of material stressed and the position and size of foot that contacts with the ground. In addition, issues with the consistency of good plate to ground contact, and variation in operator test methodologies and basic operator errors can also cause variation in the data collected Fleming et al, 2007).…”
Section: Devicesmentioning
confidence: 99%
“…The LWD, which was first developed in Germany for use in pavement foundation construction, is receiving increased attention for use in quality control/quality assurance (QC/ QA) during pavement construction (Nazzal, AbuFarsakh, Alshibli, & Mohammad, 2007). The LWD has been evaluated extensively in several European countries, notably in the United Kingdom (Fleming, Frost, & Lambert, 2007). In the United States, the device has already been evaluated in several states, including Kansas, Louisiana, Minnesota, Montana, and Virginia (Davich, Camargo, Larsen, Roberson, & Siekmeier, 2006;Hosain & Apeagyei, 2010;Mooney & Miller, 2008;Nazzal et al, 2007;Puppala, 2008;Siekmeier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%